Regional Autonomy and Agricultural Development : Regional Autonomy Policy and Agricultural Development Strategy (Articel Review) - Fikriman Fikriman; Nini Mawaddah (Fakultas Pertanian Universitas Muara Bungo, 2021)
The regional autonomy policy gives the region the freedom to take initiative in designing and developing specific local policies. Authority in agriculture is the authority bestowed on the district/city. The magnitude of authority in the district policy executor has positive and negative impacts on agricultural development. Development process implicitly requires the transformation of traditional agriculture into advanced or modern farming. The purpose of this writing is to discuss regional autonomy policies and agricultural development strategies. Advanced farming is a well-skilled farm to continuously adapt to the ever-changing challenges and market demands.Key words : policy, autonomy, strategy, development